Alternate dosage formulations of oral targeted anticancer agents. (December 2021) - Wagner, Charlotte; Adams, Val; Overley, Colleen
Objective: Oral anticancer therapies have demonstrated superior outcomes compared to traditional cytotoxic chemotherapy in many disease states. However, certain patients may not be candidates for these agents due to odynphagia or dysphagia. The purpose of this review is to summarize the data for extemporaneous compounding of oral anticancer agents. Data sources: Food and drug administration approvals of oncology agents were reviewed to identify oral anticancer therapies. In order to find alternative administration options: the package inserts of each of these agents were reviewed, each medication was searched in a tertiary drug information resource, the medical information teams of each drug manufacturer were contacted to inquire about proprietary data, sites with pediatric trials were contacted, a primary literature search was performed, and listservs for national pharmacy and oncology organizations were reviewed. Data summary: Eighty-five food and drug administration-approved oral anticancer therapies were identified to be included. Of those agents, nine (11%), had information in the package insert related to alternative administration. After further research, 46 (54%) of the agents had some information related to alternate formulations for administration. The recipes and stability of each of these compounds is included. Conclusions: The majority of agents do not have Phase I or II trials that assess safety or pharmacokinetics of alternative formulations. Clinicians should exercise caution when recommending or administering these agents outside of food and drug administration-approved indicated use and utilize clinical judgment in assessing the risks and benefits of altering anticancer compounds. However, the alternative administration considerations presented can increase access to oncology patients who have difficulty swallowing.